IMPLEMENTASI KEBIJAKAN UPAH MINIMUM KABUPATEN (UMK) DAN PENGARUHNYA TERHADAP KESEJAHTERAAN MASYARAKAT (Studi Pada Kabupaten Kebumen) - Prasetyo, Hendrawan (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2018)
Almost the average company in Kebumen Regency has applied salary payment of employees in accordance with the provisions of MSEs, although in implementation is not one hundred percent. Although Kebumen District Government has set District Minimum Wage (MSE) in 2017 amounting to Rp 1,433,900.00, but there are still many employers / companies that pay salaries under the MSEs. The relations of workers and employers actually need each other. Workers expect the fulfillment of the necessities of life and the entrepreneur seeks to maintain the survival of his company. Without employers, workers find it difficult to sustain their lives, whereas unemployed workers will not be able to continue their business. So it needs a good relationship between the two, the existence of mutual understanding. Employers need to understand the needs of the workers, and the workers understand the company's ability to pay wages. The purpose of this study is to find out how the implementation of District Minimum Wage policy and its impact on community welfare in Kebumen District. The type of this research is qualitative research, taking the data source using the technique of "purposive sampling" with the number of informants as many as 11 people including from the elements of local government that is the Office of Manpower and Cooperative SME Kebumen Regency, private entrepreneurs in Kebumen District, and employees of private companies in Kebumen . Data collection in this research is done through observation, documentation and in-depth interview. Data analysis techniques in this study is interactive model analysis, including four components of data collection, data reduction, data presentation and conclusion or verification. Theories used are theories of public policy, policy implementation and wages. The results of this study found that almost most companies in Kebumen District have paid employee salaries according to MSEs, although there are still companies that have not been able to meet the payroll of employees according to the MSEs. Some companies studied do not experience obstacles in the implementation of MSE in accordance with the established, but if the company has problems in terms of implementing payroll employees according to MSEs there is a mechanism of deferring payment. The role of local government in the implementation of MSE is needed in terms of socialization and coaching and know the problems that occur in the company or labor in the scope of Kebumen. In terms of achieving the welfare of workers, the company should be able to provide salaries in accordance with the Minimum Wage and supplemented with the provision of various benefits in order to create the welfare of workers in particular and society in general. Keywords: policy implementation, workers, company, welfare, minimum wage